Coordinación de políticas macroeconómicas en el Mercosur - FANELLI, José María corrd. (SIGLO XXI, 2001)
Contiene colaboradores: GONZALEZ ROZADA, Martín; KAIFMAN, Saúl; BARROS DE CASTRO, Antonio; PIRES DE SOUZA, Francisco E.; LORENZO, Fernando; NOYA, Nelson; DAUDE, Christian